2009
DOI: 10.1200/jco.2008.18.0182
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Reactivation in Lymphoma Patients With Prior Resolved Hepatitis B Undergoing Anticancer Therapy With or Without Rituximab

Abstract: Among HBsAg-negative/anti-HBc-positive DLBCL patients treated with R-CHOP, 25% developed HBV reactivation. Close monitoring until at least 6 months after anticancer therapy is required, with an alternative approach of prophylactic antiviral therapy to prevent this potentially fatal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
570
6
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(610 citation statements)
references
References 39 publications
18
570
6
16
Order By: Relevance
“…[18][19][20] Mortalities due to acute exacerbation of HBV in chemotherapy patients therefore occur worldwide. 4,8,24,25 To prevent acute exacerbation of HBV in chemotherapy patients, we developed a novel order entry-based therapeutic control system to increase the prechemotherapy HBV testing rate and improve the HBV prophylactic rate for chemotherapy patients. This study demonstrates that the therapeutic control system achieved a 99.3% HBV screening rate in a hospital, markedly higher than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] Mortalities due to acute exacerbation of HBV in chemotherapy patients therefore occur worldwide. 4,8,24,25 To prevent acute exacerbation of HBV in chemotherapy patients, we developed a novel order entry-based therapeutic control system to increase the prechemotherapy HBV testing rate and improve the HBV prophylactic rate for chemotherapy patients. This study demonstrates that the therapeutic control system achieved a 99.3% HBV screening rate in a hospital, markedly higher than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…(HEPATOLOGY 2015;62:387-396) 4 The incidence of HBV reactivation in patients with lymphoma and resolved hepatitis B after rituximab-based therapy ranges from 1.5% to 23.8%. [5][6][7][8] Reactivation of HBV infection in cancer patients receiving chemotherapy may cause interruption of chemotherapy and, in severe cases, lead to liver failure and death. 9-11 Additionally, the prognosis of cancer may be compromised by disruption in anticancer treatment Abbreviations: ALT, alanine aminotransferase; anti-HBc, antibody to hepatitis B core antigen; CI, confidence interval; HBsAg, hepatitis B surface antigen; HBV, hepatitis B virus; HCC, hepatocellular carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, anti-viral prophylaxis is recommended if anti-HBc is detected -even in patients lacking HBsAg -based on reports of severe HBV reactivation in this setting. 74 In any case, liver function and HBV DNA should be periodically monitored in anti-HBc-positive patients with or without anti-HBs during immunosuppressive therapy as occult HBV carriers are more frequent in this group. 1,21 WHICH ANTI-VIRAL PROPHYLAXIS SHOULD BE CHOSEN FOR IBD PATIENTS?…”
Section: How Frequent Is Progression To Liver Cirrhosis In Ibd Patienmentioning
confidence: 99%
“…11 More recently, reverse seroconversion has been reported in patients receiving biologics, and the risk has been found to be particularly high in those treated with rituximab, a monoclonal antibody against CD20 that leads to long-lasting depletion of B cells. 12 In the only prospective study, Yeo et al 12 found that 5 of 21 (24%) HBsAg-negative, anti-HBc-positive patients developed reverse seroconversion during CHOP-R chemotherapy (cyclophosphamide, doxorubicin, vincristine, prednisone, and rituximab) for diffuse large B cell lymphoma. All five cases caused severe hepatitis, including one death.…”
Section: Reverse Seroconversionmentioning
confidence: 99%